GPX4 expression changes in proximal tubule cells highlight the role of ferroptosis in IgAN - Jianbo Qing; Lijuan Zhang; Ru Fan; Huiwen Zhi; Changqun Li; Yaheng Li; Junnan Wu; Chongyang Han; Yafeng Li (Scientific Reports)
Abstract As an important mechanism of renal injury, oxidative stress (OS) is inseparable from the occurrence of renal fibrosis and the rapid progression of renal failure. However, the contribution of OS to IgA nephropathy (IgAN), the primary driver of chronic kidney disease remains uncertain. To investigate the effects of OS in IgAN, and identify the mechanisms of cell and tissue injury and protection, single-cell RNA sequencing (scRNA-seq) data and microarray data of IgAN were collected and analyzed. Through gene set variation analysis (GSVA), we identified significant alterations in the activity of multiple OS pathways within the proximal tubule cells (PTCs) of IgAN patients. Subsequent enrichment analysis revealed that the differentially expressed genes associated with OS in PTCs were primarily linked to the process of ferroptosis. Therefore, regulators of ferroptosis were collected to define the ferroptosis activity of PTCs in IgAN, and we found that the activity of suppressing ferroptosis was significantly enhanced. Moreover, being the central controller of ferroptosis, the expression of GPX4 in the PTCs of IgAN is extremely significant, which has been further verified by immunohistochemistry in kidney tissues of IgAN patients. Additionally, the GSVA of microarray data of IgAN indicated that the activity of driving ferroptosis and suppressing ferroptosis in tubulointerstitium were markedly decreased, however, the inhibition of ferroptosis in the tubulointerstitium of IgAN is relatively stronger. These findings demonstrate that ferroptosis inhibition may be a potential mechanism to alleviate OS injury in IgAN, and GPX4 could not only function as a specific marker for PTCs in IgAN but also represent a potential therapeutic target to halt the progression of the disease.